The Effect of Psychoeducational Therapy on the Self Efficacy of Children with Chemotherapy Program - Megasari, Anis Laela; Wulandari, Ika Subekti (Indonesian Journal of Global Health Research, 2024)
Chemotherapy is one of the therapy programs that must be carried out for cancer sufferers. Unfortunately, many cancer patients, especially children, are not ready to face it. This unpreparedness will certainly affect the success rate of the chemotherapy program. The aim of this research is to determine the effect of psychoeducational therapy on the level of self-efficacy of the chemotherapy process in children with cancer. This research used a pre-experimental with one group pretest post-test design. The population of this study were children diagnosed with leukemia who underwent chemotherapy at the YKAKi Halfway House Semarang in May-June 2023. The sample in this study used a total sampling of 25 respondents. Self-efficacy was measured using the self-efficacy scale instrument with validity results showing t-value > 1.96 and reliability test results showing r = 0.97. Providing psycho-educational therapy consists of four phases Bivariate analysis used the Wilcoxon statistical test. Statistical test results show a p-value of 0.001. It can be concluded that there is an influence of psychoeducational therapy on the level of self-efficacy for the chemotherapy process in children with cancer. Based on the research results, it can be concluded that providing atraumatic therapy such as psychoeducation is very important for pediatric patients undergoing chemotherapy. This aims to increase self-efficacy so that the chemotherapy program can be carried out optimally so as to improve the quality of the patient's health.